Regulatory Reform in The Era of Digital Constitutionalism - Abdulloh; Khairul Fadli Rambe; Mulia Darma (Jurnal Hukum dan Peradilan, 2026)
The digital era has permeated the legal and justice systems, posing serious challenges to constitutional justice. AI can replicate algorithmic bias and reinforce inequality. Indonesian regulations (the PDP Law and the ITE Law) are insufficient to address AI ethics and procedural justice. This gap requires a robust ethical framework for technology to be a tool of justice. This study aims to formulate ethical standards and principles based on Siyasah Dusturiyah, integrating them into Digital Constitutionalism to fill this legal void. The study uses a normative legal method (doctrinal legal research) with legislative and comparative approaches. A descriptive-comparative analysis examines the Indonesian legal framework alongside EU regulations (the EU AI Act and the GDPR) to identify best practices. Results show significant gaps in Indonesian law on AI ethics, in contrast to the EU's proactive integration of ethical standards. Thus, this study proposes adapting three principles—Ethical Impact Assessment, Human Oversight, and Right to Be Fixed—as the ethical foundation of Indonesian Digital Constitutionalism. Such adaptation is crucial to ensure accountability of digital systems and strengthen citizens' constitutional rights.